2021
DOI: 10.1002/pc.25955
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes in carbon/epoxy multiscale textile preform composites: A review

Abstract: Carbon nanotube integrated textile structural composites are one of the demanded materials especially for space/aerospace and defense industries in the 21st century due to their better damage tolerance properties compared to the metal and ceramics. This review paper exclusively performed on carbon nanotubes (CNTs) added carbon fiber/epoxy multiscale composites, including recent innovative methods of integrating CNTs to carbon filaments using the direct method such as growing on fiber, chemical grafting, and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 235 publications
(335 reference statements)
0
29
0
Order By: Relevance
“…[80][81][82][83] Meanwhile, the incorporation of nanofillers with very high strength and modulus, as a reinforcement in the polymer matrix is increasing in the current days to enhance the matrix dependent properties. [85] Due to the notable strength and stiffness properties of nanofillers like CNTs, [67,[86][87][88] graphene [89,90] and nanoclay [91,92] they are being used as secondary reinforcements for the polymer matrices of the CFRP composites, which leads to their enhanced mechanical behavior. [38,93] However, the homogeneity in the dispersion of nanofillers decides the extent of improvement in mechanical properties.…”
Section: Fibermentioning
confidence: 99%
“…[80][81][82][83] Meanwhile, the incorporation of nanofillers with very high strength and modulus, as a reinforcement in the polymer matrix is increasing in the current days to enhance the matrix dependent properties. [85] Due to the notable strength and stiffness properties of nanofillers like CNTs, [67,[86][87][88] graphene [89,90] and nanoclay [91,92] they are being used as secondary reinforcements for the polymer matrices of the CFRP composites, which leads to their enhanced mechanical behavior. [38,93] However, the homogeneity in the dispersion of nanofillers decides the extent of improvement in mechanical properties.…”
Section: Fibermentioning
confidence: 99%
“…Textile composites use reinforcement in the form of fabric (natural or synthetic) which are in woven, knitted, or braided formation. Textile reinforced composite material shows superior mechanical, electrical, thermal, and ballistic behavior with a much-reduced weight [21]. Textile composite provides aspects to organize unidirectional materials into two dimensional and three dimensional assemblies with the desired shape, dimension, and material orientation.…”
Section: Textile Composites In High Strength Applicationsmentioning
confidence: 99%
“…Graphene nanomaterials can be directly incorporated with the textile preforms including fibre, tow, and fabrics. It has been found that electrophoretic deposition (EPD) and chemical vapour deposition (CVD) methods are the most commonly used techniques to graft graphene and some other nanomaterials including amorphous carbon, carbon nano-fibres, and carbon nanotubes [ 157 ].…”
Section: Production Process Of Graphene-based Materialsmentioning
confidence: 99%